Perovskite solar cell processed by using graphdiyne structural characteristics
By inducing perovskite crystal growth as a template on the electron transport layer of perovskite solar cells, the problem of internal strain in perovskite films is solved, and the film quality and device stability are improved.
Patent Information
- Application Number
- CN202411630169.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Perovskite solar cells are subject to internal strain due to non-periodic growth during nucleation and growth, forming a large number of defects, affecting the photoelectric performance and stability of the device.
The film stress homogenization is achieved by modifying using crystalline thiophene graphiteyne on the electron transport layer as a "template" to induce perovskite crystal growth.
It improves the quality and electron transmission capabilities of perovskite films, suppresses non-radiative recombination caused by defects, and improves the photoelectric performance and stability of the device.
Smart Images

Figure CN119546030A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic material manufacturing, and in particular relates to a perovskite solar cell processed by utilizing the structural characteristics of graphyne. Background Art
[0002] In recent years, solar cells with perovskite (PSC) as the light-absorbing layer have experienced unprecedented development and are comparable to most commercial photovoltaic cells. Overall high-quality perovskite films are a prerequisite for efficient perovskite solar cells (PSCs). However, during the nucleation and growth of perovskites, the inevitable non-periodic growth leads to internal strain in the perovskite film. Strain in halide perovskites often leads to the formation of a large number of defects, which in turn cause non-radiative recombination losses. The relatively disordered onset of epitaxial growth at the buried interface is an important reason for the inhomogeneous crystallization of perovskite films. The effectiveness of stress release can be achieved by modifying the buried interface. Therefore, in order to prepare high-quality perovskite films, studying the strain engineering of the buried interface is crucial to develop effective regulation strategies.
[0003] Interface engineering using various modified materials to regulate the buried interface has been shown to be an effective strategy to release the internal strain of perovskite films. Carbon materials and their derivatives, such as carbon nanotubes, fullerenes, graphene, and graphene, have been repeatedly reported. Among them, graphene (GDY) is a sp and sp 2 Co-hybridized carbon allotropes have become a rising star due to their good electrical conductivity and strong chemical reactivity and have been widely used in PSCs. In recent years, functionalized graphyne (such as chlorine-substituted graphyne, triazine graphyne, nitrogen-doped graphyne, and oxidized graphyne) with excellent heteroatom properties have shown extraordinary optimization effects in improving the crystallinity and interfacial transport properties of perovskites. However, most of the reported multifunctionalized graphynes are prepared by a top-down strategy, which introduces heteroatoms at the expense of breaking some acetylene bonds, resulting in structural disorder and poor crystallization. At present, there is no work on modifying the buried interface to prepare high-quality films using the crystal structure characteristics of graphyne. Therefore, expanding the application of the material crystal structure and exploring the formation mechanism of the uniform film behind the improvement of device performance are of guiding significance for the subsequent application of graphyne in PSCs. Summary of the invention
[0004] The present invention aims to provide a perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material.
[0005] To achieve the above purpose, the present invention adopts the following technical solution:
[0006] A perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material includes, from bottom to top, a transparent conductive substrate, a crystalline graphyne-modified electron transport layer, a perovskite active layer, a hole transport layer, and a metal counter electrode; wherein the crystalline graphyne-modified electron transport layer is modified by using crystalline graphyne on the surface of the electron transport layer, which acts as a "template" to induce the growth of perovskite crystals and achieve film stress homogenization. On this basis, the quality and electron transport capacity of the perovskite film are improved. By suppressing the non-radiative recombination caused by defects and improving the charge extraction capacity, the photoelectric performance and stability of the device are effectively improved.
[0007] The crystalline graphyne modified electron transport layer is obtained by spin coating a crystalline graphyne dispersion on the electron transport layer and annealing.
[0008] By utilizing the lattice matching characteristics, crystalline thiophene graphyne (SGDY) was successfully introduced as a functional lattice template into the buried interface. The regular growth of perovskite crystals induced by the thiophene graphyne (SGDY) template is conducive to alleviating the excessive compressive stress caused by lattice mismatch, and finally achieving the homogenization of the internal stress of the film.
[0009] The spin coating conditions are as follows: spin coating at a speed of 3500 rpm for 40-50 seconds and then annealing at 100° C. for 5-10 minutes.
[0010] The crystalline graphyne dispersion is obtained by diluting and dispersing crystalline thiophene graphyne with anhydrous ethanol after cell disruption.
[0011] The preparation method of crystalline thiophene graphene is:
[0012] (1) In a solvent, tetrabromothiophene is coupled with trimethylethynylsilane by a Sonogashira coupling reaction, using bis(triphenylphosphine)palladium dichloride and cuprous iodide as catalysts to obtain tetrakis(trimethylethynyl)thiophene;
[0013] (2) tetra(trimethylethynyl)thiophene is treated with tetrabutylammonium fluoride in tetrahydrofuran solvent under a light-proof argon atmosphere with stirring to obtain tetraethynylthiophene;
[0014] (3) adding pyridine to tetraethynylthiophene to dissolve it, using a copper sheet as a catalyst and template, adding it dropwise into the pyridine containing the copper sheet in the dark under an argon atmosphere, and heating it to 90° C.-110° C. to react and polymerize;
[0015] (4) The product on the copper sheet is washed with acetone, 3M hydrochloric acid and anhydrous ethanol in sequence to obtain the final crystalline thiophene graphyne.
[0016] The electron transport layer is a tin oxide electron transport layer, and the preparation method of the tin oxide electron transport layer is:
[0017] (1) Preparation of tin oxide precursor solution: diluting the tin oxide colloidal solution to a dilution ratio of SnO2:H2O=1:3 (v:v), and ultrasonically dispersing the diluted solution to obtain a tin oxide precursor solution;
[0018] (2) Transparent conductive substrate: The transparent conductive substrate is ultrasonically treated with glass detergent, deionized water, acetone and isopropanol in sequence, then blown dry with nitrogen, and then treated with plasma;
[0019] (3) Preparation of tin oxide electron transport layer: The prepared tin oxide precursor solution of step (1) is spin-coated onto the glass substrate of step (2) on a coating machine, followed by annealing.
[0020] The method for preparing a perovskite solar cell using the structural characteristics of a crystalline graphyne material is as follows:
[0021] Step (1) The transparent conductive substrate is ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15-20 minutes respectively, then blown dry with nitrogen, and then treated with plasma for 15-20 minutes;
[0022] Step (2) spin coating the tin oxide precursor solution onto the glass substrate of step (1) at a rotation speed of 3500 rpm for 30-40 seconds, annealing at 150° C. for 20-30 minutes, and then cooling to room temperature for standby use;
[0023] Step (3) spin coating the crystalline graphyne dispersion onto the tin oxide electron transport layer of step (2) at a rotation speed of 3500 rpm for 30-40 seconds, and annealing at 100° C. for 5-10 minutes;
[0024] Step (4) The perovskite layer is deposited by spin coating a perovskite precursor solution at a rotation speed of 5000 rpm for 40-60 seconds, and 200 μL of ethyl acetate anti-solvent is injected in the last 10-15 seconds to form a film of the perovskite precursor solution, and then annealed at 100° C. for 50-60 minutes to obtain an active layer; Step (5) Spin coating a passivation layer precursor solution on the perovskite active layer in step (4) at 4000 rpm for 20-30 seconds.
[0025] In step (6), the hole transport layer is obtained by spin coating the Spiro-OMeTAD precursor solution at a rotation speed of 4000 rpm for 30-40 seconds, and the perovskite device is aged after spin coating.
[0026] Step (7) sequentially vapor-deposit molybdenum oxide and silver electrodes on the perovskite device that has been aged in step (6), thereby obtaining a perovskite solar cell that is processed using the structural characteristics of the crystalline graphyne material.
[0027] The perovskite precursor solution in step (4) is obtained by adding cesium iodide (CsI), methylamine chloride (MACl), methylamine iodide (MAI), formamidine iodide (FAI), and lead iodide (PbI2) in a molar ratio of 0.05:0.20:0.10:1.40:1.68 to a mixed solution of DMF and DMSO (DMF:DMSO=4:1, v:v).
[0028] The passivation layer precursor solution in step (5) is an isopropanol solution of phenethylammonium iodide (PEAI).
[0029] The Spiro-OMeTAD precursor solution in step (6) uses chlorobenzene as a solvent, and each 1000 μL of the solvent contains 80-100 mg of Spiro-OMeTAD powder, 30-40 μL of tetra-tert-butylpyridine solution, and 40-50 μL of acetonitrile solution containing lithium bis-trifluoromethanesulfonyl imide.
[0030] Principle of the invention:
[0031] The present invention introduces highly crystalline thiophene graphene (SGDY) into the buried interface to regulate the film strain. For the first time, the structural characteristics of functionalized SGDY are utilized, and the growth of perovskite crystals is induced by using crystalline SGDY as a "template". The lattice matching of crystalline SGDY and perovskite crystals realizes the homogenization of the internal stress of the film, while improving the quality of the perovskite film, it also promotes the extraction and transmission of charges at the interface, and finally realizes the preparation of high-performance and high-stability perovskite solar cell devices.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) Based on the property that the structure of graphyne can be regulated by heteroatom functionalization, the present invention prepares crystalline thiophene graphyne through a "bottom-up" approach, avoiding the introduction of heteroatoms at the expense of breaking some acetylene bonds, and exhibits good polymerization regularity.
[0034] (2) The thiophene graphyne of the present invention has good crystallization properties and matches the lattice parameters of perovskite (FAPbI3). The unique structural characteristics of thiophene graphyne materials are used as an electron transport layer and a perovskite active layer modification, and as a "template" to induce the growth of perovskite crystals and release excessive stress inside the film. The internal stress of the film is homogenized, and the quality of the perovskite film is improved.
[0035] (3) The present invention is the first to utilize the structural characteristics of graphyne materials to regulate the performance of perovskite solar cells. By utilizing the high lattice matching between crystalline thiophene graphyne and the 001 surface of perovskite, a buried interface is introduced to induce the growth of perovskite crystals.
[0036] (4) The present invention realizes strain regulation in perovskite film by using the buried interface modification strategy and the high lattice matching characteristics of crystalline thiophene graphyne. As a functional lattice template of perovskite crystals at the buried interface, the growth of high-quality perovskite film is induced and the stress inhomogeneity inside the film is alleviated. This is conducive to the preparation of high-performance and high-stability perovskite solar cells. At the same time, the present invention has a low production cost and a simple preparation method, which is more conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the perovskite device structure and stress release regulation mechanism in the present invention.
[0038] Figure 2 HRTEM image of crystalline SGDY and elemental mapping of C and S in the present invention (the inset is the HRTEM image of the interlayer spacing of SGDY)
[0039] Figure 3 The XRD pattern of the crystalline SGDY in the present invention and the HRTEM image of its corresponding lattice constant.
[0040] Figure 4 XRD patterns of the inventive and crystalline SGDY-optimized perovskite films and the scratched stress-free perovskite powder.
[0041] Figure 5 2D GIWAXS patterns of perovskite films optimized for the inventive target and crystalline SGDY at different incident angles from 0.1° to 3.6°
[0042] Figure 6 1D GIWAXS patterns of the optimized perovskite films for the standard and crystalline SGDY in the present invention at different incident angles from 0.1° to 2°.
[0043] Figure 7 These are the top surface morphology images of the standard and crystalline SGDY optimized perovskite films obtained by SEM and AFM in the present invention.
[0044] Figure 8 These are buried interface morphology images of the standard and crystalline SGDY-optimized perovskite film obtained by SEM and AFM in the present invention.
[0045] Fig. 9 Cross-sectional SEM images of the PSC device optimized for the standard sample and crystalline SGDY in the present invention.
[0046] Fig.10 PL spectra and TRPL spectra of the perovskite films deposited on SnO2 and SnO2 / SGDY in the present invention.
[0047] Fig.11 JV curves of the forward and reverse scans of the standard parts and the crystalline SGDY optimized device of the present invention
[0048] Fig.12 This is the long-term stability test curve of the unpackaged standard and crystalline SGDY optimized device in N2 atmosphere. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but these embodiments do not limit the scope of the present invention.
[0050] The present invention is a perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne materials, including a transparent conductive substrate, an electron transport layer modified by crystalline graphyne, a perovskite active layer, a hole transport layer and a metal counter electrode deposited sequentially from bottom to top. The surface of the tin oxide electron transport layer is modified by using crystalline graphyne materials, and the material is subjected to cell crushing treatment and then the dispersion in ethanol is spin-coated on the tin oxide substrate. The perovskite light absorption layer is prepared by using organic-inorganic halide perovskite, the hole transport layer is prepared by using Spiro-OMeTAD, and a metal Ag electrode is used as a counter electrode.
[0051] Example 1
[0052] Combination Figure 1 Schematic diagram of the device structure.
[0053] Step (1): A commercially purchased transparent conductive substrate was ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15 minutes respectively, then dried with nitrogen gas, and then treated with plasma for 15 minutes.
[0054] Step (2): Spin-coat the prepared tin oxide precursor solution onto the treated glass substrate on a coating machine at a speed of 3500 rpm for 30 seconds, place it on a hot plate at 150° C. for annealing for 30 minutes, and then cool it to room temperature for use;
[0055] The tin oxide solution is prepared by diluting a tin oxide colloidal solution (15% aqueous colloidal dispersion) at a dilution ratio of SnO2:H2O=1:3 (v:v), and ultrasonically dispersing the diluted solution for 15 minutes.
[0056] Step (3): spin-coating the crystalline graphyne dispersion onto the tin oxide electron transport layer on a coating machine at a rotation speed of 3500 rpm for 30 seconds, and then annealing at 100° C. for 5 minutes;
[0057] The crystalline graphyne dispersion is obtained by diluting and dispersing crystalline thiophene graphyne with anhydrous ethanol after cell crushing.
[0058] The preparation method of crystalline thiophene graphene is as follows: tetrabromothiophene (1g, 2.5mmol) is added to triethylamine (60mL) and stirred to dissolve. Under the protection of Ar atmosphere, trimethylsilyl acetylene (1.47g, 15mmol), bis(triphenylphosphine) palladium dichloride (53mg, 0.075mmol) and cuprous iodide (14mg, 0.075mmol) are added. The reaction is heated at 80°C and stirred for 24h. After the reaction is completed, water is added to the mixed solution and extracted with dichloromethane. After drying with anhydrous sodium sulfate, the solvent is evaporated by rotary evaporation. Purification by silica gel column chromatography gives a light yellow powder, which is tetrakis(trimethylethynyl)thiophene. Under a light-proof Ar atmosphere, 2,3,4,5-tetrakis[(trimethylsilyl)ethynyl]-thiophene (20 mg, 0.044 mmol) was dissolved in tetrahydrofuran (THF) (30 ml), and 0.25 ml of tetrabutylammonium fluoride (TBAF) (1M THF, 0.25 mmol) was injected therein. The reaction mixture was stirred at 8°C for 10 min, then washed with saturated brine and ethyl acetate, dried with anhydrous sodium sulfate, and the solvent was evaporated under vacuum to obtain tetraethynylthiophene; 30 ml of pyridine was added to tetraethynylthiophene to dissolve it, and in a dark Ar atmosphere, it was added dropwise to 70 ml of pyridine containing copper foil, and the reaction mixture was heated at 110°C. After three days of reaction, the copper foil was removed; the product on the copper sheet was ultrasonically cleaned with acetone, 3M hydrochloric acid, and anhydrous ethanol in turn, and the black powder obtained after drying was crystalline thiophene Graphyne.
[0059] Step (4): on the basis of the above-mentioned crystalline graphyne modified layer, a perovskite precursor solution is deposited by spin coating at a rotation speed of 5000 rpm for 40 seconds, and 200 μL of ethyl acetate anti-solvent is injected in the penultimate 10 seconds to form a film of the perovskite precursor solution, followed by annealing at 100° C. for 60 minutes in a glove box to obtain a perovskite active layer film;
[0060] The perovskite precursor solution is prepared by adding cesium iodide (CsI), methylamine chloride (MACl), methylamine iodide (MAI), formamidine iodide (FAI), and lead iodide (PbI2) in a molar ratio of 0.05:0.20:0.10:1.40:1.68 to a mixed solution of DMF and DMSO (DMF:DMSO=4:1, v:v), and stirring overnight to obtain a perovskite precursor solution.
[0061] Step (5): Spin-coat the passivation layer precursor solution on the perovskite active layer at 4000 rpm for 20 seconds;
[0062] The passivation layer precursor solution is an isopropanol solution of 2 mg / ml phenylethylammonium iodide (PEAI).
[0063] Step (6): The hole transport layer is obtained by spin coating the Spiro-OMeTAD precursor solution at a speed of 4000 rpm for 30 seconds. The spin-coated perovskite device is placed in a constant temperature and humidity drying oven for aging for 17 hours;
[0064] The Spiro-OMeTAD precursor solution uses chlorobenzene as a solvent. Each 1000 μL of the solvent contains 90 mg of Spiro-OMeTAD powder, 37 μL of tetra-tert-butylpyridine solution, and 44 μL of acetonitrile solution containing lithium bis-trifluoromethanesulfonyl imide (260 mg / mL). After mixing, the mixture is continuously shaken on a vortex oscillator for 2 hours to fully dissolve and obtain a Spiro-OMeTAD precursor solution.
[0065] Step (7): Place the aged perovskite device into a mask with suitable specifications and use a vacuum coating machine to coat the perovskite device with a thickness of at least 1×10 -7 Under the high vacuum conditions of Pa, 8nm of molybdenum oxide and 100nm of silver electrode are evaporated in sequence to obtain the prepared perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that no crystalline graphyne modification layer is provided, and the other steps are the same as those in Example 1, specifically:
[0068] Step (1): A commercially purchased transparent conductive substrate was ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15 minutes respectively, then dried with nitrogen gas, and then treated with plasma for 15 minutes.
[0069] Step (2): Spin-coat the prepared tin oxide precursor solution onto the treated transparent conductive substrate on a coating machine at a speed of 3500 rpm for 30 seconds, place it on a hot plate at 150° C. for annealing for 30 minutes, and then cool it to room temperature for use;
[0070] The tin oxide solution is prepared by diluting a tin oxide colloidal solution (15% aqueous colloidal dispersion) at a dilution ratio of SnO2:H2O=1:3 (v:v), and ultrasonically dispersing the diluted solution for 15 minutes.
[0071] Step (3): The perovskite layer is deposited by spin coating the precursor solution at a rotation speed of 5000 rpm for 40 seconds. In the last 10 seconds, 200 μL of ethyl acetate anti-solvent is injected to form a film of the perovskite precursor solution. The film is then annealed at 100° C. for 60 minutes in a glove box to obtain a perovskite active layer film.
[0072] The perovskite precursor solution is prepared by adding cesium iodide (CsI), methylamine chloride (MACl), methylamine iodide (MAI), formamidine iodide (FAI), and lead iodide (PbI2) in a molar ratio of 0.05:0.20:0.10:1.40:1.68 to a mixed solution of DMF and DMSO (DMF:DMSO=4:1, v:v), and stirring overnight to obtain a perovskite precursor solution.
[0073] Step (4): spin coating a passivation layer precursor solution on the perovskite active layer at 4000 rpm for 20 seconds;
[0074] The passivation layer precursor solution is an isopropanol solution of 2 mg / ml phenylethylammonium iodide (PEAI).
[0075] Step (5): The hole transport layer is obtained by spin coating the Spiro-OMeTAD precursor solution at a speed of 4000 rpm for 30 seconds. The spin-coated perovskite device is placed in a constant temperature and humidity drying oven for aging for 17 hours;
[0076] The Spiro-OMeTAD precursor solution uses chlorobenzene as a solvent. Each 1000 μL of the solvent contains 90 mg of Spiro-OMeTAD powder, 37 μL of tetra-tert-butylpyridine solution, and 44 μL of acetonitrile solution containing lithium bis-trifluoromethanesulfonyl imide (260 mg / mL). After mixing, the mixture is continuously shaken on a vortex oscillator for 2 hours to fully dissolve and obtain a Spiro-OMeTAD precursor solution.
[0077] Step (6): Place the aged perovskite device into a mask with suitable specifications and use a vacuum coater to coat the device with a thickness of at least 1×10 -7 Under the high vacuum conditions of Pa, 8nm of molybdenum oxide and 100nm of silver electrode are evaporated in sequence to obtain the prepared perovskite solar cell.
[0078] The above embodiments and control examples were tested for performance.
[0079] like Figure 2 As shown, the HRTEM image of the thiophene graphyne material observed curved stripes with a lattice spacing of 0.38nm, which can be attributed to the interlayer distance of thiophene graphyne (SGDY), which is consistent with the characteristics of graphyne-based materials. In addition, the uniform distribution of C and S elements in SGDY corresponds well to the elemental map, proving that the material was successfully prepared.
[0080] pass Figure 3 The structural characteristics of SGDY were studied by HRTEM and XRD pattern measurements, such as Figure 3As shown, the SGDY material prepared by this method exhibits a highly crystalline state. After the peak values in the XRD spectrum are calculated according to the Bragg law (q = 2π / d), the diffraction spacings of different crystal planes obtained correspond well in the HRTEM image. At the same time, the diffraction spots obtained by fast Fourier transform of the corresponding selected area prove the hexagonal lattice structure of the material and well define the structural information of the crystalline SGDY. The most important thing is that the plane d spacing value of the crystal plane corresponding to the peak at 14.74° is 0.60nm, which is one of the dominant crystal planes and perfectly matches the (001) crystal plane (d = 0.632nm) of the perovskite.
[0081] like Figure 4 As shown, the XRD peak (001) plane of the standard perovskite film moves to a high diffraction angle relative to the scratched stress-free perovskite powder, which proves that the film is subjected to a large compressive strain. Based on this, the crystalline SGDY functional lattice template of the present invention is introduced into the buried interface, and the lattice parameters with a high lattice matching rate provide a more orderly start for the three-dimensional periodic epitaxial growth of the perovskite lattice. With the optimization of the crystalline SGDY, the peak position of the (001) plane shifts to a lower angle, proving that the compressive strain has been effectively relieved.
[0082] Grazing-incidence wide-angle X-ray scattering (GIWAXS) was performed to investigate the residual strain release in various dimensions. A range of incident angles from 0.1° to 3.6° was used to investigate the depth-dependent microstructure of the films, and the corresponding 1D GIWAXS patterns were obtained by orientation integration of the 2D patterns. Figure 5 As shown in Figure 1, the perovskite grows along the vertical orientation. After the introduction of SGDY optimization, the overall scattering intensity is significantly improved without affecting the dominant crystal orientation, indicating that the overall film crystallinity is improved, which corresponds well to the XRD results. Figure 6As shown in the figure, the in-plane (qxy) and out-of-plane (qz) diffraction peaks were further extracted, where the in-plane direction is parallel to the substrate, reflecting the (010) crystal plane; the out-of-plane direction is perpendicular to the substrate, reflecting the (001) crystal plane. In the in-plane direction, as the incident angle increases, the peak moves to the right and the lattice constant decreases, reflecting the increase in compressive strain. This is caused by the higher compressive strain caused by the substrate restricting the crystal growth. As the crystal gradually grows upward, the deformation freedom increases, resulting in a gradient decrease in the compressive strain. Due to excessive residual stress, the deformation of the perovskite octahedral lattice causes the lattice to gradually expand from the top surface to the inside of the film in the out-of-plane direction. This severe crystallization heterogeneity caused by residual stress in both the in-plane and out-of-plane directions is the culprit for the existence of a large number of structural defects, affecting the overall perovskite film quality. After the introduction of crystalline SGDY to the buried interface, consistent peaks were shown at different film depths, both in the in-plane and out-of-plane directions, indicating that the lattice distortion in all dimensions has disappeared. The crystalline material as a functional substrate template induces the subsequent perovskite crystal growth, adjusting the stress inside the entire film to achieve uniform growth of perovskite crystals.
[0083] To check the crystallization state of the perovskite film, the standard and crystalline SGDY-optimized films were directly observed from all directions using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Figure 7 As shown in the figure, the upper surface morphology of the perovskite film of the standard piece clearly shows wrinkles due to extrusion, which is caused by strong compressive strain. After the stress is eliminated, the upper surface morphology image is smooth and flat, which is consistent with the AFM results. In addition, after the introduction of crystalline SGDY regulation, the grain size increases and is evenly distributed, while the residual PbI2 clusters decrease. The exposed buried interface morphology can intuitively show that the crystalline SGDY optimization effectively reduces the pinhole-like gaps and the film is denser ( Figure 8 ). The dense perovskite film exhibits high hydrophobicity, which is the key to improving the stability of the device. Cross-sectional SEM image of the perovskite film ( Fig. 9 ) also showed the overall vertical growth and quality improvement of the film crystals, which is mutually confirmed by the increase in the intensity of the XRD characteristic peaks. The reason for achieving the above performance is that the stress homogenization achieved after lattice matching regulates the growth of perovskite crystals. The fewer grain boundaries and pinholes in the optimized film, the less non-radiative recombination losses caused by structural defects, which is beneficial to reducing the Voc loss in PSC. At the same time, the flat morphology at the buried interface provides a good foundation for the subsequent deposition of the perovskite layer, which is conducive to better longitudinal orderly growth of the crystal.
[0084] To demonstrate the effect of crystalline SGDY on the electron extraction and transfer process between SnO2 and perovskite, steady-state photoluminescence (PL) and time-resolved photoluminescence (TRPL) were performed on perovskite films deposited on SnO and SnO / TGD substrates. Fig.10 As shown, the optimized film produced a stronger PL quenching effect, which indicates that it has a higher electron extraction ability. In addition, the TRPL spectra of the two perovskite films were characterized and fitted using a double exponential decay equation. Compared with 26.52ns of the tin oxide / perovskite film, the decay time of the optimized crystalline SGDY is shorter, 14.22ns, and the electron extraction ability is stronger, which is consistent with the PL results.
[0085] The device performance and stability were further tested under simulated sunlight using perovskite solar cell devices. A planar heterojunction solar cell with a FTO / SnO2 / perovskite / Spiro OMeTAD / MoO3 / Ag structure was prepared. By optimizing the buried crystalline SGDY modification concentration, the best photovoltaic performance was obtained, and the PCE was significantly improved. Fig.11 The current density versus voltage (JV) curve of the best PSC is shown. The optimized device shows a mitigated hysteresis phenomenon. The hysteresis index (HI) is reduced from 3.42% to 2.69%. Stability is one of the important criteria for evaluating device performance. The present invention tests the PCE data of unpackaged devices stored in a nitrogen atmosphere at room temperature for a long time. Fig.12 It can be seen that after 2000 h, the PCE value of the optimized device still remains above 90% of the initial value, indicating that the regularly grown perovskite crystals caused by the homogeneous lattice stress are the key reason for the improved stability.
[0086] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A perovskite solar cell processed using the structural characteristics of crystalline graphyne material, characterized in that: The solar cell includes, from bottom to top, a transparent conductive substrate, a crystalline graphyne-modified electron transport layer, a perovskite active layer, a hole transport layer and a metal counter electrode; the crystalline graphyne-modified electron transport layer is modified by using crystalline graphyne on the surface of the electron transport layer, which acts as a "template" to induce the growth of perovskite crystals and achieve film stress homogenization.
2. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 1, characterized in that: The crystalline graphyne modified electron transport layer is obtained by spin coating a crystalline graphyne dispersion on the electron transport layer and annealing.
3. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 2, characterized in that: The spin coating conditions are: spin coating at a speed of 3500 rpm for 30-40 seconds and then annealing at 100° C. for 5-10 minutes.
4. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 2, characterized in that: The crystalline graphyne dispersion is obtained by diluting and dispersing crystalline thiophene graphyne with anhydrous ethanol after cell disruption.
5. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 4, characterized in that: The preparation method of crystalline thiophene graphene is: (1) In a solvent, tetrabromothiophene is coupled with trimethylethynylsilane by a Sonogashira coupling reaction, using bis(triphenylphosphine)palladium dichloride and cuprous iodide as catalysts to obtain tetrakis(trimethylethynyl)thiophene; (2) tetra(trimethylethynyl)thiophene is treated with tetrabutylammonium fluoride in tetrahydrofuran solvent under a light-proof argon atmosphere with stirring to obtain tetraethynylthiophene; (3) adding pyridine to tetraethynylthiophene to dissolve it, using a copper sheet as a catalyst and template, adding it dropwise into the pyridine containing the copper sheet in the dark under an argon atmosphere, and heating it to 90° C.-110° C. to react and polymerize; (4) The product on the copper sheet is washed with acetone, 3M hydrochloric acid and anhydrous ethanol in sequence to obtain the final crystalline thiophene graphyne.
6. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 1, characterized in that: The electron transport layer is a tin oxide electron transport layer, and the preparation method of the tin oxide electron transport layer is: (1) Preparation of tin oxide precursor solution: diluting the tin oxide colloidal solution to a dilution ratio of SnO2:H2O=1:3 (v:v), and ultrasonically dispersing the diluted solution to obtain a tin oxide precursor solution; (2) Transparent conductive substrate: The transparent conductive substrate is ultrasonically treated with glass detergent, deionized water, acetone and isopropanol in sequence, then blown dry with nitrogen, and then treated with plasma; (3) Preparation of tin oxide electron transport layer: The prepared tin oxide precursor solution of step (1) is spin-coated onto the glass substrate of step (2) on a coating machine, followed by annealing.
7. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 1, characterized in that: Step (1) The transparent conductive substrate is ultrasonically treated with glass detergent, deionized water, acetone and isopropanol for 15-20 minutes respectively, then blown dry with nitrogen, and then treated with plasma for 15-20 minutes; Step (2) spin coating the tin oxide precursor solution onto the glass substrate of step (1) at a rotation speed of 3500 rpm for 30-40 seconds, annealing at 150° C. for 20-30 minutes, and then cooling to room temperature for standby use; Step (3) spin coating the crystalline graphyne dispersion onto the tin oxide electron transport layer of step (2) at a rotation speed of 3500 rpm for 30-40 seconds, and annealing at 100° C. for 5-10 minutes; Step (4) The perovskite layer is deposited by spin coating a perovskite precursor solution at a rotation speed of 5000 rpm for 40-60 seconds, and 200 μL of ethyl acetate anti-solvent is injected in the last 10-15 seconds to form a film of the perovskite precursor solution, and then annealed at 100° C. for 50-60 minutes to obtain an active layer; Step (5) Spin coating a passivation layer precursor solution on the perovskite active layer in step (4) at 4000 rpm for 20-30 seconds. In step (6), the hole transport layer is obtained by spin coating the Spiro-OMeTAD precursor solution at a rotation speed of 4000 rpm for 30-40 seconds, and the perovskite device is aged after spin coating. Step (7) sequentially vapor-deposit molybdenum oxide and silver electrodes on the perovskite device that has been aged in step (6), thereby obtaining a perovskite solar cell that is processed using the structural characteristics of the crystalline graphyne material.
8. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 7, characterized in that: The perovskite precursor solution in step (4) is obtained by adding cesium iodide (CsI), methylamine chloride (MACl), methylamine iodide (MAI), formamidine iodide (FAI), and lead iodide (PbI2) in a molar ratio of 0.05:0.20:0.10:1.40:1.68 to a mixed solution of DMF and DMSO (DMF:DMSO=4:1, v:v).
9. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 7, characterized in that: The passivation layer precursor solution in step (5) is an isopropanol solution of phenethylammonium iodide (PEAI).
10. The perovskite solar cell processed by utilizing the structural characteristics of crystalline graphyne material according to claim 7, characterized in that: The Spiro-OMeTAD precursor solution in step (6) uses chlorobenzene as a solvent, and each 1000 μL of the solvent contains 80-100 mg of Spiro-OMeTAD powder, 30-40 μL of tetra-tert-butylpyridine solution, and 40-50 μL of acetonitrile solution containing lithium bis-trifluoromethanesulfonyl imide.
Citation Information
Patent Citations
Solar laminated cell based on graphdiyne electron transfer layer and preparation method
CN109860221A
Stannic dioxide / graphdiyne compound interface layer and preparation and application thereof
CN110817860A